The impact of hypoestrogenism and occlusal function on MMP1, MMP8 and MMP13 expression in the odontogenic region in rats (Research, Society and Development, 2021)
Background: The impact of estrogen deficiency and occlusion in the matrix metalloproteinases (MMPs) expression in dental tissues has not yet been elucidated. Objective: To evaluate the influence of estrogen deficiency and occlusal hypofunction and hyperfunction on the gene expression of MMP1, MMP8 and MMP13 in the odontogenic region of teeth in continuous growth, in the murine model. Material and methods: Rats (Wistar Hannover lineage) were divided into two groups according to the intervention received: Hypoestrogenism Group - ovariectomy surgery and Control Group - fictitious surgery. Occlusal hypofunction and hyperfunction conditions were also established in all animals (each animal presented both conditions). After euthanasia, the hemimandibles were removed to evaluate the gene expression through real time PCR. T-test was used to compare the mean differences between groups (P0.05). A statistically significant difference of the relative MMP13 expression between the occlusal hypofunction and hyperfunction tooth was observed (P=0.03). In the hypoestrogenism group, MMP13 was overexpressed in hypofunction tooth (P=0.045). Conclusion: Occlusal function affects MMP13 expression in the odontogenic region, in murine model.